De Pygmaeorum bellis sive de argumento antiquo in carmen heroico-comicum converso - Sacré, Dirk (My University, 2014)
De Pygmaeorum bellis sive de argumento antiquo in carmen heroico-comicum converso The theme of the battle or the war between the Pygmies and the cranes is an ancient one. Homer already alludes to it in the Iliad. Various testimonies make clear that it was dealt with in a Greek poem which must have had some similarity with the famous Batrachomyomachia. Later Greek and Latin authors offer bits of information about the Pygmies, the cranes and the alleged origins of their conflicts, as well as the vicissitudes of their battles. Not unsurprisingly, some modern authors, writing either in the vernacular or in Latin, have tried to fill the gap and have written on the theme. In Neo-Latin poetry the most famous treatment of it was the Pugmaio-geranomachia written around the end of the seventeenth century by the famous English Neo-Latin poet Joseph Addison (1672-1719), a mock-epic highly admired in the eighteenth and nineteenth centuries. In France, Théodule Paillard-Fernel (1807-1877) wrote another Latin poem on these battles: his Latin poem (bearing the French title Combat mémorable entre les pygmées et les grues), dating from 1824, was undoubtedly inspired by Addison. Prior to these two poets, Jacques Moireau, an priest of the Oratory (1622-1666) who lived and worked in France, wrote a Neo-Latin epic with the title Pygmaeidos libri VIII sive poëtica classicae iuventutis paegnia, which, however, did not influence or inspire in any way Addison or Paillard-Fernel. Moireau’s Pygmaeis, though issued two times (Vendôme 1676 and Angers 1682), remains completely unknown to modern Neo-Latin scholars: thus, it is absent from Ludwig Braun’s recent (2007) catalogue and survey of Neo-Latin epic in France, 1500-1700. Moireau’s Pygmaeis is an out-of-the-ordinary epic poem. Contrary to Addison and Paillard-Fernel, this poet did not treat the theme in a serious way, so as to make the reader smile at the funny contrast between the elevated style of the epic and the insignificance of its protagonists; instead, he wrote a burlesque poem – a genre of poetry which in itself is rather exceptional in Neo-Latin literature – undermining both the contents and the style of traditional epic poetry. Thus, he proceeded in exactly the same way in Latin as Scarron did in French; not by coincidence, it is said that Scarron has been influenced by Moireau, a point which would require further study, since virtually nothing is known about Moireau’s life and activities. Since the poem remains unexplored until the present day, a survey of the contents of the eight books opens the presentation of the work. The rest of the talk deals with the characteristics of the poem and highlights some of its most funny passages. Thus attention is paid to the absolutely not heroic character of many of its ‘heroes’ (actually, it happens that female warriors are depicted as being more brave), the anachronisms adorning the poem (thus the poem, the time of action of which is situated in ancient Greek history, features such characters as a cowardly Cicero, the printer Plantin, the cartographer Ortelius, the humanists Despauterius and Lambinus, the scientist Galileo Galilei, a Turkish immigrant called Mustapha, etc.), the parody of epic commonplaces (e.g. the very wittily perverted descriptions of sunrise and sunset, or the council of the Gods), the insertion of truisms, and the subversion of the epic style itself (Moireau deliberately uses a mixture of styles, and noticeably introduces trivial images, words that are not fitting into the high style of epic, and semi-Latin vocabulary).
Keywords: Filología clásica; Batrachomyomachia; Pugmaio-geranomachia; Pygmaeidos libri VIII sive poëtica classicae iuventutis paegnia; Pygmaeis; Heroes